Tinjauan Hukum Islam Terhadap Penerapan Akad As-Salam dalam Transaksi E-Commerce - Fadhli, Ashabul (IAIN Samarinda, 2016)
The rapid development of technology have been showing new dimension for transaction activity.Â The early of transaction activity with traditional method. Now day, it can be done by networking fast, is so called with internet (e-commerce). In the practice, e-commerce transaction involving some parties which niet found in the traditional method. As well as on the shape, process up to end of transaction. As an approval that emerged from agreement, akad have legal consequence that given the right and the other side requires the obligation to the parties that form a binding contract to one anether. Therefore, akad was essential to the acceptance or rejection of legal act.